Correction to: Are industry-funded charities promoting "advocacy-led studies" or "evidence-based science"?: a case study of the International Life Sciences Institute - Sarah Steele; Gary Ruskin; Lejla Sarcevic; Martin McKee; David Stuckler (BMC, 2019)
Since the publication of this article [1], the journal and the authors have received further context about the position of ILSI on the issue with the ILSI Mexico branch.